Business model adaptation through inclusion of environmental sustainability measures - Aleš Krmela; Mariana Tesařová (Trends Economics and Management, 2020)
Purpose of the article: The article aims at understanding and description of how and why the business model (BM) of an incumbent manufacturing B2B company adapts, collaboratively with a dominant customer, through measures leading to an improved environmental sustainability performance. The research question was: How is a business model of an incumbent, businessto- business company adapted through the inclusion of environmental sustainability measures, with the customer's involvement? Methodology/Methods: A qualitative research approach, drawing on a descriptive-explanatory, single case study conducted on a Czech manufacturing company active in the field of steel processing was performed. The study draws on the analysis of the focal company's internal and external documents related to sustainability, as well as on semi-structured interviews with the examined company's executives. The analysis also include the externally available sustainability related documents of a dominant customer. Scientific Aim: Understanding the impact of the environment-related sustainability measures on the adaptation of the extant BM of the focal company, and the role a dominant customer plays in the process. Findings: The inclusion of environment-related sustainability measures leads to an adaptation of the process and the product, as well as of the focal company's BM and most of its key elements. A value capture by the focal company has been identified as the mainly affected element of a BM through both cost savings and a more business gained. The element value proposition adapts towards a "greener company". The core logic of the BM remains unchanged. Conclusions: B2B incumbent companies implement environmental sustainability measures into their BMs, aiming to contribute to the preservation of the environment. The economic side continues to be carefully considered. It can even be a trigger of implementation. The large customers get strongly involved in the process, contributing to the adaptation of all four key elements of the BM. The BM's adaptation happens dynamically, in incremental steps.
Keywords: L21; L22; L61; O14; O31; O32; O33; 650; business model; business model adaptation; sustainability; environmental sustainability